GOOGLE CLASSROOM READINESS OF JUNIOR HIGH SCHOOL STUDENTS IN LEARNING ENGLISH - Risa Anggraini; Nursyah Handayani; Enni Maisaroh; Sekar Kinanti Rahajeng (Journal MELT (Medium for English Language Teaching), 2022)
AbstractThe corona virus has hit almost the whole world, including Indonesia. This pandemic has been going on for almost 3 years. This pandemic has destroyed almost all sectors, both in the economy and in education. So this makes students to study at home (online) including students in Medan. So the researchers conduct online survey at SMP Bina Satria Mulia Medan. The purpose of this research is to find out students’ readiness on E- Learning through Google Classroom during Covid. Therefore, the researchers conduct the study by using survey research design with Likert Scale to get the data by sending the questionnaires to 28 students. There are differences in students' technological readiness before and after learning through the application of Google Classroom. Before learning, the category was less ready and after learning the implementation of Google Classroom had a ready category. Based on this analysis, the implementation of Google Classroom on students' technological readiness for English material at Bina Satria Mulia Medan has technology readiness in the ready category. English has a very important influence for students both as communication tools with foreign speakers and also has a very important role to support students in studying other fields of study. Therefore, the curriculum developed now aims to be able to prepare students to have competencies. Key word —Google Classroom, Covid - 19, E- Leaning, Students’ Readiness,English